Effects of Individualized Gait Rehabilitation Robotics for Gait Training on Hemiplegic Patients: Before-After Study in the Same Person - Guo, Zhao; Ye, Jing; Zhang, Shisheng; Xu, Lanshuai; Chen, Gong; Guan, Xiao; Li, Yongqiang; Zhang, Zhimian (Frontiers in Neurorobotics, 2022)
Background: Lower-limb exoskeleton robots are being widely used in gait rehabilitation training for stroke patients. However, most of the current rehabilitation robots are guided by predestined gait trajectories, which are often different from the actual gait trajectories of specific patients. One solution is to train patients using individualized gait trajectories generated from the physical parameters of patients. Hence, we aimed to explore the effect of individual gaits on energy consumption situation during gait rehabilitation training for hemiplegic patient with lower-limb exoskeleton robot. Methods: 9 unilateral-hemiplegic patients were recruited for a two-day experiment. On the first day of the experiment, the 9 patients were guided by a lower-limb exoskeleton robot, walking on flat ground for 15 minutes in general gait trajectory, which was gained by CGA (clinical gait analysis) method. On the other day, the same 9 patients wore the identical robot and walked on the same flat ground for 15 minutes in an individualized gait trajectory. The main physiological parameters including heart rate (HR) and peripheral capillary oxygen saturation (SpO2) were acquired via cardiotachometer and oximeter before and after the walking training. The energy consumption situation was indicated by the variation of the value of HR and SpO2 after walking training compared to before. Results: Between-group comparison showed that the individualized gait trajectory training resulted in an increase in HR levels and a decrease in SpO2 levels compared to the general gait trajectory training. The resulting difference had a statistical significance of p<0.05. Conclusion: Using individualized gait guidance in rehabilitation walking training can significantly improve energy efficiency for hemiplegic patient with stroke.